2018
DOI: 10.1021/acs.joc.8b00393
|View full text |Cite
|
Sign up to set email alerts
|

TfOH- and HBF4-Mediated Formal Cycloisomerizations and [4+3] Cycloadditions of Allene-alkynylbenzenes

Abstract: A metal-free, TfOH (1.1 equiv)-mediated formal cycloisomerization of easily prepared allene-alkynylbenzenes to give pyrrolidines and cyclopentanes derivatives was developed. This reaction is initiated by the generation of allylic cation from allene, followed by alkyne's reaction with the allylic cation, to give a vinyl cation, which is finally intercepted by the triflate (TfO) anion. This cycloisomerization can be further tuned to become an acid-mediated intramolecular formal [4+3] cycloaddition by using 10 eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The resulting mixture was then cooled to room temperature, diluted with ethyl acetate (10 mL), and filtered through a short column of silica gel (eluent: ethyl acetate (2×10 mL)). After evaporation of the solvent, the crude residue was purified by column chromatography on silica gel (petroleum ether/ethyl acetate=25/1 (500 mL)) to afford 1 m (0.3746 g, 34%): solid; m.p. 100.7–101.4 °C ( n ‐hexane/DCM); 1 H NMR (300 MHz, CDCl 3 ) δ 7.77 (d, J =8.4 Hz, 2H, ArH), 7.36–7.16 (m, 5H, ArH), 7.12–6.98 (m, 2H, ArH), 4.97–4.87 (m, 1H, CH=), 4.38 (s, 2H, CH 2 ), 3.86 (d, J =7.2 Hz, 2H, CH 2 ), 2.32 (s, 3H, CH 3 ), 2.18–2.00 (m, 4H, CH 2 ×2), 1.65–1.37 (m, 6H, CH 2 ×3); 13 C NMR (75 MHz, CDCl 3 ) δ 200.8, 143.3, 136.0, 131.4, 129.5, 128.2, 128.0, 127.7, 122.4, 104.1, 85.4, 83.5, 81.7, 47.0, 36.3, 31.2, 27.1, 25.9, 21.4; IR (neat) ν (cm −1 ) 2928, 2853, 2241, 1965, 1598, 1490, 1443, 1350, 1305, 1264, 1235, 1163, 1094, 1031, 1019; MS (70 ev, EI) m/z (%) 406 (M + +1, 5.97), 405 (M + , 19.89), 91 (100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting mixture was then cooled to room temperature, diluted with ethyl acetate (10 mL), and filtered through a short column of silica gel (eluent: ethyl acetate (2×10 mL)). After evaporation of the solvent, the crude residue was purified by column chromatography on silica gel (petroleum ether/ethyl acetate=25/1 (500 mL)) to afford 1 m (0.3746 g, 34%): solid; m.p. 100.7–101.4 °C ( n ‐hexane/DCM); 1 H NMR (300 MHz, CDCl 3 ) δ 7.77 (d, J =8.4 Hz, 2H, ArH), 7.36–7.16 (m, 5H, ArH), 7.12–6.98 (m, 2H, ArH), 4.97–4.87 (m, 1H, CH=), 4.38 (s, 2H, CH 2 ), 3.86 (d, J =7.2 Hz, 2H, CH 2 ), 2.32 (s, 3H, CH 3 ), 2.18–2.00 (m, 4H, CH 2 ×2), 1.65–1.37 (m, 6H, CH 2 ×3); 13 C NMR (75 MHz, CDCl 3 ) δ 200.8, 143.3, 136.0, 131.4, 129.5, 128.2, 128.0, 127.7, 122.4, 104.1, 85.4, 83.5, 81.7, 47.0, 36.3, 31.2, 27.1, 25.9, 21.4; IR (neat) ν (cm −1 ) 2928, 2853, 2241, 1965, 1598, 1490, 1443, 1350, 1305, 1264, 1235, 1163, 1094, 1031, 1019; MS (70 ev, EI) m/z (%) 406 (M + +1, 5.97), 405 (M + , 19.89), 91 (100).…”
Section: Methodsmentioning
confidence: 99%
“…After evaporation of the solvent, the crude residue was purified by column chromatography on silica gel (petroleum ether/ethyl acetate = 25/1 (500 mL)) to afford 1 m [28] 8, 143.3, 136.0, 131.4, 129.5, 128.2, 128.0, 127.7, 122.4, 104.1, 85.4, 83.5, 81.7, 47.0, 36.3, 31.2, 27.1, 25.9, 21.4; IR (neat) ν (cm À 1 ) 2928, 2853,2241,1965,1598,1490,1443,1350,1305,1264,1235,1163,1094,1031 The Schlenk tube was dried under vacuum with a heating gun until the white CdI 2 turned to yellow green and refilled with N 2 for three times.…”
Section: N-(44-pentamethylene-23-butadienyl)-n-(3-phenylprop-2-yn-1mentioning
confidence: 99%
“…Upon exposure to Brøsted acids such as TfOH (1.1 equiv) and HBF 4 (6.0 equiv), yne‐allenes 99 underwent formal cycloisomerization toward pyrrolidines and cyclopentanes 101 . [ 113 ] Interestingly, the presence of 10.0 equiv of TfOH or 6—15 equiv of HBF 4 made yne‐allenes 99 to convert into seven‐membered carbocycles 100 through cycloisomerization and Friedel‐Crafts reaction cascade. A series of yne‐allenes with different substituents at both aromatic ring and allene moiety were proven to be workable for this approach.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…The performed dehydration experiments indicated the tetrafluoroboric acid-diethyl ether complex to be a suitable tool for the preparation of cyclobutenyl bromides and chlorides. A review of the literature revealed various applications of tetrafluoroboric acid, including Hosomi-Sakurai allylation and Prins cyclization, 32 cycloisomerizations, 33 polycyclizations, 34 syntheses of diarylmethyl tetrafluoroborates, 35 Fischer indole synthesis, 36 Meyer-Schuster-like rearrangement, 37 ring closures of aryl C-glycosides, 38 the cross-coupling of trifluoroborates with benzhydryl alcohols, 39 and more. 40 Due to the lack of prior attempts to use the tetrafluoroboric acid-diethyl ether complex for the dehydration of alcohols, we studied the behavior of commonly available alcohols in the presence of the tetrafluoroboric acid-diethyl ether complex.…”
Section: Accepted Manuscriptmentioning
confidence: 99%